2015
DOI: 10.3390/ma8073945
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Digital Impressions and Fitness of Single Crowns Based on Digital Impressions

Abstract: In this study, the accuracy (precision and trueness) of digital impressions and the fitness of single crowns manufactured based on digital impressions were evaluated. #14-17 epoxy resin dentitions were made, while full-crown preparations of extracted natural teeth were embedded at #16. (1) To assess precision, deviations among repeated scan models made by intraoral scanner TRIOS and MHT and model scanner D700 and inEos were calculated through best-fit algorithm and three-dimensional (3D) comparison. Root mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 34 publications
3
39
0
Order By: Relevance
“…In previous studies, natural tooth-shaped models manually prepared by the researcher or full-arch dentiforms were used to test the accuracy and precision of intraoral scanners 6,9,14,20,23,24) . Alongside the development of various types of intraoral scanners, multiple studies have been conducted on their accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, natural tooth-shaped models manually prepared by the researcher or full-arch dentiforms were used to test the accuracy and precision of intraoral scanners 6,9,14,20,23,24) . Alongside the development of various types of intraoral scanners, multiple studies have been conducted on their accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have estimated the accuracy and precision of intraoral scanners using various shaped objects such as customized inlay cavity models, natural tooth-shaped models, and full-arch dentiform models [10][11][12][13][14][15][16][17] . However, the precision and accuracy measurement of the oral scanner differs between each researcher because of differences in scanning models; thus, the interpretations of the measured precision and accuracy have been variously expressed.…”
Section: Introductionmentioning
confidence: 99%
“…According to the available evidence, accuracy of IOS‐derived digital models is clinically acceptable and comparable to that of conventional models (Albdour et al, ; Hack, ; Nedelcu, Olsson, Nyström, Rydén, & Thor, ; Rossini, Parrini, Castroflorio, Deregibus, & Debernardi, ). The trueness of an IOS can be assessed by registering the 3D images on a reference model obtained by a high‐resolution industrial optical scanner, articulated arm, coordinate measuring machine, or micro‐computed tomography (µCT) (Ahlholm, Sipilä, Vallittu, Jakonen, & Kotiranta, ; Aragón, Pontes, Bichara, Flores‐Mir, & Normando, ; Chochlidakis et al, ; Goracci, Franchi, Vichi, & Ferrari, ; Imburgia et al, ; Yang, Lv, Liu, Si, & Feng, ). At the same instance, the accuracy of CBCT images has been confirmed utilizing various devices (Baumgaertel, Palomo, Palomo, & Hans, ; Lascala, Panella, & Marques, ); however, the accuracy of CBCT‐derived digital models has not yet been assessed adequately (Engelbrecht, Fourie, Damstra, Gerrits, & Ren, ).…”
Section: Introductionmentioning
confidence: 99%
“…38 Findings from this study are also in agreement with those from studies published by Alqahtani 9 (marginal gap = 60 μm) and Xang et al 10 (marginal gap = 58 μm). In the Alqahtani and Xang et al studies, 9,10 a Trios intraoral scanner and 3Shape design software were used to record and to design the crowns; however, the main differences between the aforementioned studies and this study are that in the aforementioned studies, no information was reported for the settings for the design software, and a 5-axis milling machine (Zenotec; Ivoclar Vivadent) was used to fabricate the crowns. 9,10 The result of the current study also aligns with that of the current authors' previous study, where a mean marginal gap of 59.7 μm was reported for the lithium disilicate crowns scanned, designed, and manufactured using the same protocol as the current study.…”
Section: Figurementioning
confidence: 94%
“…Even though American Dental Association specification No. 8 suggests a marginal gap of 25 to 40 μm for cemented crowns, clinically acceptable complete coverage crowns reported marginal gaps ranging from 58 to 200 μm . However, the larger the marginal gap, the thicker the luting agent will be at the margin, the faster the rate of its degradation, and the lower the fracture resistance of the complete coverage crown .…”
mentioning
confidence: 99%